Итоги охранных раскопок Западного некрополя Херсонеса Таврического в 1995 г. - Магда, А. В.; Дмитриев, В. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Magda A. V., Dmitriev V. A. Results of Security Excavation of West Necropolis in Chersonesus of Tauride in 1995